A STRUCTURAL NARRATIVE ANALYSIS ON BAHAU PEOPLE’S MYTH OF BATOQ AYAU - Jonathan Irene Sartika Dewi Max (Fakultas Ilmu Budaya, Universitas Mulawarman, 2021)
The Myth of Batoq Ayau is one of popular folklores of Dayak Bahau People in East Kalimantan. The narrative is first examined using narrative theory to find out the way plot is structured. Secondly, the binary oppositions which arranged to build the meaning of the myth are unveiled by a structuralist approach. This research is conducted with a qualitative descriptive methodology. It is found that the myth develops a plot of tragedy where a new equilibrium is settled in the end. The binary oppositions are examined from three elements of narrative which are the characters, the conflicts, and the setting. Eight binary opposition pairs develop the meaning of the myth. They are Safety-Danger, Outsider-Insider, Sturdiness- Defenselessness, Physical-Psychological, Cautiousness-Negligence, Life-Death, and Low-High. Thus, the meaning delivered myth of Batoq Ayau still has a relevancy to the condition of human beings today where being vigilance to the environment issues is truly needed.